Seedling structure of Euphorbia L. and Chamaesyce Gray species - doi: 10.4025/actascibiolsci.v36i1.18601 - Luiz Antonio de Souza; Higor Simionato Dariva; Luciane da Silva Santos; Eloiza Muniz Capparros (Acta Scientiarum. Biological Sciences, 2013)
Chamaesyce prostrata (Aiton) Small, Euphorbia heterophylla L. and Euphorbia graminea Jacq. are weedy species that occur with relative frequency in the region of Maringá, Paraná State, Brazil. Data about the morphology and anatomy of seedlings of these species were obtained, with emphasis on significant structural differences of seedlings between species of Euphorbia and Chamaesyce. Seedlings are phanerocotylar and epigeal. Root is axial and triarch. Cotyledons are leaf-like and dorsiventral. Eophylls and prophylls are simple and dorsiventral. Morphological variations occur in the cotyledon shape of Euphorbia seedlings. It is remarkable the Kranz structure of leaves that occurs only in Chamaesyce.